A Glutamate Dependent Redox System in Blood Cells is Integral for Phagocytosis in Drosophila melanogaster - Gonzalez, Elizabeth A. (2013)
Glutamate transport is highly regulated as glutamate directly acts as a neurotransmitter [1-3] and indirectly regulates the synthesis of antioxidants [4-5]. Although glutamate deregulation has been repeatedly linked to serious human diseases such as HIV infection and Alzheimer's [6-8], glutamate's role in the immune system is still poorly understood. We find that a putative glutamate transporter in Drosophila melanogaster, polyphemus (polyph), plays an integral part in the fly's immune response. Flies with a disrupted polyph gene exhibit decreased phagocytosis of microbial-derived bioparticles. When infected with S.aureus, polyph flies show an increase in both susceptibility and bacterial growth. Additionally, the expression of two known glutamate transporters, genderblind and excitatory amino acid transporter 1, in blood cells affects the flies’ ability to phagocytose and survive following an infection. Consistent with previous data showing a regulatory role for glutamate transport in the synthesis of the major antioxidant glutathione, polyph flies produce more reactive oxygen species (ROS) as compared to wildtype when exposed to S.aureus. In conclusion, we demonstrate that a polyph-dependent redox system in blood cells is necessary to maintain the cells’ immune-related functions. Furthermore, our model provides insight into how deregulation of glutamate transport may play a role in disease.